Diagnostic accuracy of perfusion-weighted phase-resolved functional lung magnetic resonance imaging in patients with chronic pulmonary embolism - Duan, Jianghui; Xie, Sheng; Sun, Hongliang; An, Jing; Li, Huan; Li, Ling; Grimm, Robert; Voskrebenzev, Andreas; Vogel-Claussen, Jens (Frontiers in Medicine, 2023)
This study aimed to evaluate the diagnostic performance of perfusion-weighted phaseresolved functional lung (PW-PREFUL) magnetic resonance imaging (MRI) in patients with chronic pulmonary embolism (CPE).This study included 86 patients with suspected chronic thromboembolic pulmonary hypertension (CTEPH), who underwent PREFUL MRI and ventilation/perfusion (V/Q) single-photon emission computed tomography/computed tomography (SPECT/CT). PREFUL MRI was performed at 1.5T using a balanced steady-state free precession sequence during free breathing.Color-coded PW images and quantitative parameters were obtained by postprocessing. Meanwhile, V/Q SPECT/CT imaging was performed as a reference standard. Hypoperfused areas in the lungs were scored for each lobe and segment using V/Q SPECT/CT images and PW-PREFUL MR images, respectively. Normalized perfusion (QN) and perfusion defect percentage (QDP) were calculated for all slices. For intra-and interobserver variability, the MRI images were analyzed 2 months after the first analysis by the same radiologist and another radiologist (11 years of lung MRI experience) blinded to the results of the first reader.Results: Of the 86 enrolled patients, 77 met the inclusion criteria (36 diagnosed with CPE using V/Q SPECT/CT and 41 diagnosed with non-CPE etiology). For the PW-PREFUL MRI, the sensitivity, specificity, accuracy, and positive and negative predictive values for the diagnosis of CPE were 97%, 95%, 96%, 95%, and 98% at the patient level; 91%, 94%, 93%, 91%, and 94% at the lobe level, and 85%, 94%, 92%, 88%, and 94% at the segment level, respectively. The detection of segmental and subsegmental hypoperfusion using PW-PREFUL MRI revealed a moderate agreement with V/Q SPECT/CT (κ = 0.65; 95% confidence interval: 0.61-0.68). The quantitative results indicated that the QN was lower in the CPE group than in the non-CPE group [median score (interquartile range, IQR) 6.3 (2.8-9.2) vs 13.0 (6.2-13.5), P < .001], and the QDP was higher [median score (IQR) 33.8 (15.7-51.7) vs 2.2 (1.4-2.9), P < .001].PREFUL MRI could be an alternative test to detect CPE without requiring breath-hold, contrast agents, or ionizing radiation.